Nickel and dimed : on (not) getting by in America - Ehrenreich, Barbara (New York, N.Y. : Henry Holt, 2002)
Millions of Americans work full-time, year-round, for poverty-level wages. In 1998, Barbara Ehrenreich decided to join them. She was inspired in part by the rhetoric surrounding welfare reform, which promised that a job -- any job -- could be the ticket to a better life. But how does anyone survive, let alone prosper, on six to seven dollars an hour? To find out, Ehrenreich left her home, took the cheapest lodgings she could find, and accepted whatever jobs she was offered as a woefully inexperienced homemaker returning to the workforce. So began a grueling, hair raising, and darkly funny odyssey through the underside of working America. Moving from Florida to Maine to Minnesota, Ehrenreich worked as a waitress, a hotel maid, a cleaning woman, a nursing home aide, and a Wal-Mart sales clerk. Very quickly, she discovered that no job is truly "unskilled, " that even the lowliest occupations require exhausting mental and muscular effort. She also learned that one job is not enough; you need at least two if you intend to live indoors.
Introduction: Getting ready -- Serving in Florida -- Scrubbing in Maine -- Selling in Minnesota -- Evaluation -- Reader's guide.
"A Metropolitan/Owl book."
Includes bibliographical references.
Keywords: Minimum wage -- United States; Unskilled labor -- United States; Poverty -- United States; Working poor -- United States; Popular Works [Publication Type]